1983
DOI: 10.1159/000249826
|View full text |Cite
|
Sign up to set email alerts
|

Functional Studies of Sessile Macrophages in Liver and Spleen of Psoriatics

Abstract: In 24 psoriatics of either sex aged between 22 and 84 years, functional analysis of sessile macrophages in liver and spleen revealed an accelerated metabolic elimination of Tc-99m labeled human serum albumin millimicrospheres. In psoriatics treated with aromatic retinoid, macrophage activity in liver and spleen was found to be normalized compared to the group of systemically nontreated psoriatics. 3 psoriatics with cirrhosis of the liver demonstrated an unequivocally delayed tracer accumulation in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…It has not been possible pre viously to measure monocyte activation by a serum pro tein. Our findings are in accordance with those measuring increased activity of the reticuloendothelial system [24,25] as well as of different monocyte functions in psoriasis including chemotaxis [14,15], aggregation [16], release of lysosomal enzymes [18], phagocytosis [17], angiogenic capability [23], respiratory burst [20,21] and concentration of energy-providing glucose-6-phosphate dehydrogenase activity [19], Increased levels of sCD14 arc not, however, specific for psoriasis as other disorders such as sepsis, poly trauma. endotoxin shock.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has not been possible pre viously to measure monocyte activation by a serum pro tein. Our findings are in accordance with those measuring increased activity of the reticuloendothelial system [24,25] as well as of different monocyte functions in psoriasis including chemotaxis [14,15], aggregation [16], release of lysosomal enzymes [18], phagocytosis [17], angiogenic capability [23], respiratory burst [20,21] and concentration of energy-providing glucose-6-phosphate dehydrogenase activity [19], Increased levels of sCD14 arc not, however, specific for psoriasis as other disorders such as sepsis, poly trauma. endotoxin shock.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, enhanced activity of sessile marcophages in liver and spleen, and an extension of bone marrow space have been reported in psoriasis [24,25]. It was of interest, therefore, to further study sCD14 in psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Zlatkov et al 20 observed, in 60 patients with generalized psoriasis, a decrease in arachidonic and linolenic acid concentrations, an increase in palmitic and stearic acid concentrations, and an increase in hepatic enzyme activity analogous to the changes that occur in hepatic steatosis. Altmeyer et al 3 found that psoriatics had accelerated elimination of Tc 99 -labeled albumin from circulation by macrophages resident in the liver and spleen. Macrophage activity was normalized by treatment with aromatic retinoids.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Changes in liver biopsy findings were first reported in 1954 by Dioglotti et al 10 later, Zachariae 4 described steatosis, periportal inflammatory infiltration, and focal necrosis. Similarly, Nyfors and Poulsen 6 and Roenigk et al 7 found that psoriatic patients showed a full range of pathologic changes, including cellular necrosis, fatty metamorphosis, periportal inflammation, fibrosis, and cirrhosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation